Mood Instability Is a Precursor of Relationship and Marital Difficulties: Results from Prospective Data from the British Health and Lifestyle Surveys - Bowen, Rudy Cecil; Dong, Lisa Yue; Peters, Evyn McMillan; Baetz, Marilyn; Balbuena, Lloyd (Frontiers in Psychiatry, 2017)
The DSM system implies that affective instability is caused by reactivity to interpersonal events. We used the British Health and Lifestyle Survey (HALS) that surveyed community residents in 1984 and again in 1991 to study competing hypotheses: that mood instability (MI) leads to interpersonal difficulties or vice versa. We analyzed data from 5,352 persons who participated in both waves of the survey. Factor analysis of the Eysenck Personality Inventory neuroticism scale was used to derive a 4 item scale for MI. We used depression measures that were previously derived by factor analyzing the General Health Questionnaire. We tested the competing hypotheses by regressing variables at follow-up against baseline variables. The results showed that MI in 1984 clearly predicted the development of interpersonal problems in 1991. After adjusting for depression, depression becomes the main predictor of spousal difficulties, but MI remains a predictor of interpersonal difficulties with family and friends. Attempts to investigate the reverse hypothesis were ambiguous. The clinical implication is that when MI and interpersonal problems are reported, the MI should be treated first, or at least concurrently.